System Analysis Theory Applied for Development of Microalgae Processes and Photobioreactors in the Frame of Integral Biorefinery Concept - Alexander Dimitrov Kroumov; Maya Margaritova Zaharieva; Hristo Miladinov Najdenski (International Journal Bioautomation)
Microalgae technology involves many steps of unit operations and is connected with global warming and pandemic problems because of the unique features of algal cells. Studying sophisticated systems cannot be without special mathematical tools and approaches that combine knowledge from many research areas. The system analysis theory applied in biotechnology with great success can be applied by principles of analogy to microalgae cultivation of cells in CO2 fixation from flue gases in innovative closed photobioreactors (PBRs) where the products of biomass can have performed antimicrobial, anticancer, antiviral and other activities by challenging chemical agents. Recently, a multifunctional algology laboratory was created at the Stephan Angeloff Institute of Microbiology by applying knowledge in state of the art. The goal of this work was to summarize the 40 years of experience of the authors in this area and to show how this was realized by innovative engineering solutions for studying and developing the microalgae system. Special attention was paid to the development of hybrid, innovative PBRs with the aim of fully revealing the potential of microalgae strains not only for the complete absorption of CO2 from flue gases but also for the synthesis of high-value products (HVP) with antimicrobial, antiviral and anticancer activity.